Recombinant expression of backbone‐cyclized polypeptides. Issue 5 (19th September 2013) - Borra, Radhika; Camarero, Julio A.; Craik, David J.
ABSTRACT Here we review the different biochemical approaches available for the expression of backbone‐cyclized polypeptides, including peptides and proteins. These methods allow for the production of circular polypeptides either in vitro or in vivo using standard recombinant DNA expression techniques. Polypeptide circularization provides a valuable tool to study the effects of topology on protein stability and folding kinetics. Furthermore, having biosynthetic access to backbone‐cyclized polypeptides makes the production of genetically encoded libraries of cyclic polypeptides possible. The production of such libraries, which was previously restricted to the domain of synthetic chemistry, now offers biologists access to highly diverse and stable molecular libraries that can be screened using high‐throughput methods for the rapid selection of novel cyclic polypeptide sequences with new biological activities. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 502–509, 2013.